Exploring the Knowledge Transfer Barriers and the Control Mechanisms in ERP Consulting Practice: A Systematic Literature Review of the Consultant Perspective - Zhang, Jun (Auckland University of Technology, 2022)
In recent decades, the Enterprise Resource Planning (ERP) system has been adopted by more and more transnational companies to improve their business practice. Meanwhile, most companies introduced external expert ERP consultants to help their ERP implementation. Therefore, knowledge transfer between ERP consultants and clients has become one of the significant factors impacting the success of ERP implementation. The purpose of this dissertation is to systematically review the existing literature and classify the factors examined in previous studies that influence knowledge transfer in ERP implementation. This research analyzes the ERP knowledge transfer barriers through a systematic literature review. It is essential to understand these factors and the mechanism to reduce the negative effects of the barriers. The study identifies knowledge transfer barriers as tacit knowledge, factors related to sources of knowledge transfer (namely sender and recipient), relational factors of consultant and client, and organizational cultural factors. This dissertation describes how these knowledge transfer barriers generate and influence knowledge transfer in ERP implementation. The dissertation also proposes a framework to overcome these barriers. It is essential to understand these factors and the mechanism to reduce the negative effects of the barriers. The results of this study will guide the ERP managers to focus on how to improve the effectiveness of knowledge transfer, select appropriate internal key users and external professional consultants, and master the development of positive organizational culture and relationships between consultants and clients.
Keywords: Knowledge transfer; Knowledge transfer barriers; Enterprise Resource Plan (ERP); Consultant; Enterprise system